ANALISIS ASUHAN KEPERAWATAN LANSIA DIABETES MELLITUS DENGAN MASALAH PERFUSI JARINGAN PERIFER TIDAK EFEKTIF MELALUI SENAM KAKI - Ni Kade Ayu Puspa Purwasih; Ni Made Dwi Ayu Martini (Forind Press, 2026)
Diabetes Mellitus (DM) in the elderly is a chronic health problem that often causes complications, one of which is impaired peripheral tissue perfusion that may lead to decreased mobility, risk of diabetic ulcers, and even amputation. Elderly individuals with comorbidities and genetic factors have a higher risk of peripheral circulation disorders. One of the non-pharmacological interventions that nurses can provide is diabetic foot exercise aimed at improving peripheral blood flow and neuromuscular function of the lower extremities. This scientific paper aims to analyze nursing care in depth in one elderly patient with Diabetes Mellitus, namely Mr. A, who had a history of chronic disease and family factors, with the nursing problem of ineffective peripheral tissue perfusion through the provision of foot exercises. The method used was a case study with a nursing care approach including assessment, diagnosis, intervention, implementation, and evaluation. The results showed improvement in Mr. A’s peripheral perfusion after diabetic foot exercises were performed for three sessions, with a duration of approximately 15–20 minutes in each session, indicated by reduced tingling complaints, improved acral condition, increased peripheral pulse strength, and increased Ankle Brachial Index (ABI) value. Diabetic foot exercise proved effective as an independent nursing intervention in improving peripheral tissue perfusion in elderly patients with Diabetes Mellitus.